Metagame Planeta Jovem: Transformando jovens em sua melhor versão - Gularte, Daniel; Oliveira, Mauro; Ramos, Sílvio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This article is an experience report that presents the theoretical foundations, methodologies and operational management of a multimedia solution used as an extension project in secondary school units in municipalities in Ceará for three months. Named, Planeta Jovem, the project used game technologies using narratives inspired by the goals of sustainable development to develop socio-emotional skills in program participants that are capable of changing their perception of the world to na individual with more relevance to their territory.